The Role of Digital Literacy and Digital Com-Munication in Marketing Strategies on The Performance of Private Universities in Tangerang City - Hesti Umiyati; Umi Narimawati; H.M. Yani Syafei (Green Publisher Indonesia, 2024)
In the current digital era, the role of digital literacy and digital communication is becoming increasingly important for various sectors, including higher education. Higher education institutions need to adapt to developments in information and communication technology (ICT) to improve their performance and competitiveness. One way to improve higher education performance is by implementing effective marketing strategies. The aim of this research is to analyze the role of digital literacy and digital communication in marketing strategies on the performance of Private Universities (PTS) in Tangerang City. This research uses quantitative research methods. Data was collected through surveys using questionnaires and literature studies. The data that has been collected is then analyzed using a regression test using the SPSS program. The research results show that digital literacy and digital communication in marketing strategies have a positive and significant effect on the performance of private universities in Tangerang City. Increasing digital literacy and digital communication can help / PTS develop more effective marketing strategies, so that it can improve PTS performance.